Effects of naphthalene acetic acid on yield attributes and yield of two varieties of rice (Oryza sativa L.) - Adam, AMM Golam; Jahan, Nargis (Bangladesh Journal of Botany, 2011)
Effects of 100 and 200 ppm of naphthalene acetic acid (NAA) on yield attributes and yield of two varieties of rice during 2009 - 2010 Boro season were evaluated. The highest plant height was observed due to 200 ppm in both BRRI dhan-29 (V1) and BRRI dhan-50 (V2). Number of tillers per plant were found to increase due to 100 ppm NAA only in BRRI dhan-29 and varied non-significantly. Yield attributes, viz. number of branches per panicle, number of grains per panicle and filled grains per panicle increased in BRRI dhan-29, following both 100 and 200 ppm NAA, whereas, most of the yield parameters decreased in BRRI dhan-50. Due to 100 and 200 ppm NAA, grain yield per plant increased by 27.67 and 6.85%, respectively in BRRI dhan-29 though not statistically significant. However, in BRRI dhan-50 grain yield per plant decreased by 26.54% due to 100 ppm and 27.67% due to 200 ppm. Out of the two concentrations 100 ppm NAA produced better stimulation. Key words: Rice; Naphthalene acetic acid; Foliar application; Yield DOI: http://dx.doi.org/10.3329/bjb.v40i1.8004 Bangladesh J. Bot. 40(1): 97-100, 2011 (June)